2019
DOI: 10.1155/2019/2491927
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Common Risk Factors and Mechanisms of Cardio-Cerebrovascular Ischemia and Depression

Abstract: The public health sector faces a huge challenge as a result of the high prevalence and burden of disability caused by ischemic cardio-cerebrovascular disease (CVD) and depression. Although studies have explored the underlying mechanisms and potential therapies to address conditions, there is no treatment breakthrough, especially for depression which is highly influenced by social stressors. However, accumulating evidence reveals that CVD and depression are correlated and share common risk factors, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 141 publications
(155 reference statements)
0
41
0
2
Order By: Relevance
“…Cardiovascular disease (CVD) has the highest mortality in the world [ 1 ]. With the aging of the population and the increasing incidence of obesity and diabetes, the cost of treatment for CVD will significantly increase worldwide [ 2 ]. The incidence of CVD is related to gender, and premenopausal women have a lower incidence of hypertension, atherosclerosis, myocardial dysfunction, ventricular hypertrophy, heart failure, and myocardial ischemia than age-matched men [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) has the highest mortality in the world [ 1 ]. With the aging of the population and the increasing incidence of obesity and diabetes, the cost of treatment for CVD will significantly increase worldwide [ 2 ]. The incidence of CVD is related to gender, and premenopausal women have a lower incidence of hypertension, atherosclerosis, myocardial dysfunction, ventricular hypertrophy, heart failure, and myocardial ischemia than age-matched men [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…NOX2 activation is mediated by the assembly of four cytoplasmic proteins (p67phox, p40phox, p47phox, and Rac2) with two transmembrane proteins (gp91phox and p22phox), and the activated NOX2 catalyzes oxygen to superoxide through NADPH. 3 Oxidative Medicine and Cellular Longevity WT mice after 72 h of reperfusion, which further indicated that the inhibition or deficiency of NOX2 induced a neuroprotective effect rather than delaying the progression of postischemic brain injury [46]. In a study by De Silva et al, NOX2-deficient mice that underwent 0.5 h of cerebral ischemia and 23.5 h of reperfusion were compared with wild-type mice, and they found that NOX2 deficiency was neuroprotective in the early stage of cerebral ischemia [47].…”
Section: The Role Of Nox In Ischemic Strokementioning
confidence: 99%
“…Ischemic stroke is by far the most common type of stroke [1] and poses a significant global burden on healthcare. While mortality has improved due to improvements in acute care, poststroke cognitive impairment is an increasing sequela that may eventually develop into dementia [2], and the high prevalence of depression among stroke survivors [3] remains a striking repercussion of stroke, not only with respect to the individual patient but also with respect to the caregivers and healthcare systems as well. Thrombolysis and endovascular therapy are mainstays of contemporary acute stroke treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been paid to redox and inflammatory biomarkers, because oxidative stress and increased cytokine formation play a key role in stroke pathogenesis [ 12 , 13 ]. Indeed, oxygen free radicals are responsible for the oxidation of neuronal lipids, proteins, and nucleic acids, which in turn contributes to oxidative damage of the brain [ 3 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%